Selected Decisions (6th Ed). (Selected Decisions; Issue, Year, 1972)
This volume, entitled Selected Decisions of the IMF and Selected Documents, follows the Fifth Issue of Selected Decisions of the Executive Directors and Selected Documents. The change in title has been made because of the inclusion of more Resolutions of the Board of Governors of the Fund than in the preceding volume. The present volume contains selected decisions and interpretations of the Executive Directors and resolutions of the Board of Governors of the IMF adopted prior to September 30, 1972, as well as certain selected documents of the Fund and of the United Nations to which frequent reference is made. With few exceptions, the decisions are of a general nature and relate to certain obligations, policies, and procedures under the Articles of Agreement. This issue contains most of the decisions that were published in earlier issues (September 1962, September 1963, January 1965, April 1970, and July 1971), and general decisions taken since then.